Complete nucleotide sequence of strawberry vein banding virus Chinese isolate and infectivity of its full-length DNA clone. Issue 1 (December 2016) - Feng, Mingfeng; Zhang, Hanping; Pan, Yuan; Hu, Yahui; Chen, Jing; Zuo, Dengpan; Jiang, Tong
Abstract Background Strawberry vein banding virus (SVBV) is a double-stranded DNA plant virus, which has been found in North America, Australia, Brazil, Japan, Europe and several provinces of China. Infected strawberry plants exhibit mild vein-banding symptoms and chlorosis along the veins. It is one of the most economically important diseases in Asiatic, European and North American strawberry-growing areas. Findings The complete genome of an SVBV Chinese isolate (SVBV-CN) was isolated and cloned from a naturally infected strawberry (Fragaria × ananassa cv. Sachinoka) sample found in Shenyang city of Liaoning province. Sequence analysis revealed a complete genome of 7864 nucleotides (nts) that indicated SVBV-CN was most closely related to SVBV from the United States (SVBV-US) with a sequence similarity of 85.8 %. Two major clades were identified based on phylogenetic analysis of the complete genome sequences of caulimoviruses. SVBV-CN clustered together with SVBV-US, whereas other caulimoviruses formed a separate branch. Agrobacterium-mediated inoculation ofFragaria vesca with an infectious clone of SVBV-CN results in systemic infection with distinct symptoms of yellowing bands along the main leaf veins. This suggests that the SVBV-CN infectious clone can recapitulate the symptoms observed in naturally infected strawberries, and therefore is likely the causal agent of the original disease observed in strawberries. Furthermore, strawberry plants inoculated with the infectious clone using vacuum infiltration developed symptoms with a very high infection rate of 86–100 % in 4-5 weeks post-inoculation. This compares to an infection rate of 20–40 % in 8–9 weeks post-inoculation using syringe-inoculation. Conclusions The complete nucleotide sequence of SVBV from a naturally infected strawberry was determined. Agroinfiltration of strawberry plants using an infectious clone of SVBV-CN resulted in symptoms typically found in infected strawberries from Shenyang city of Liaoning province in China. This is the first report describing an infectious clone of SVBV-CN, and that vacuum infiltration can be potentially used as a new and highly efficient means for inoculation of strawberry plants.